Analysis of Problems in Implementing Character Education at the Islamic Elementary School Level - Baiq Laksmining Prayatni; Ramli Ramli; Ramdhani Sucilestari (Academia Edu Cendekia Indonesia (AEDUCIA), 2025)
Background: This study aims to identify the challenges in implementing character education in Islamic Elementary Schools. Method: A qualitative research approach was used, conducted at MI Al-Ittihadul Islamiyah, Ampenan, in 2022. The research subjects included teachers and students. Data were collected through observation, interviews, and documentation. The data analysis process involved three steps: data reduction, data display, and conclusion drawing/verification. Result: The implementation of character education at MI Al-Ittihadul Islamiyah Ampenan has been relatively effective, integrating character education into school management, learning activities, and extracurricular programs. Conclusion: Character education in Islamic Elementary Schools can be successfully implemented through a holistic approach involving school administration, curriculum integration, and student engagement in extracurricular activities. Contribution: This study serves as a reference for future research on character education implementation, particularly in Islamic Elementary Schools.